Optimization of structural patterns for tall buildings: The case of diagrid. (15th September 2018) - Tomei, Valentina; Imbimbo, Maura; Mele, Elena
Highlights: A design strategy for diagrid tall buildings based on sizing optimization is proposed. Different geometrical patterns for diagrid structures are explored. The patterns are compared in terms of structural weight and structural performance. Abstract: Diagrid structures have recently emerged as a new solution for tall buildings which merges inherent structural efficiency, decorative qualities and morphological versatility. In this paper a design strategy based on sizing optimization techniques is proposed as either an alternative to, or a refinement of, the preliminary sizing methods suggested in literature for regular diagrids. In addition, the approach here provided can also be used for complex and non conventional patterns, as opposite to the existing procedures that mainly deal with regular geometries. Different geometrical patterns (regular, variable angle, variable density) for diagrid structures are explored, together with a fully non uniform diagrid-like pattern which mimics the principal stress trajectories on the building façade. Strategies for the generation, preliminary design and structural optimization are proposed for the different patterns; in particular the optimization process is treated with mono-objective genetic algorithms, by minimizing the structural weight and imposing a constraint condition on the lateral stiffness of the building. Thorough comparisons, both among the patterns, and between the outcomes of the preliminary design procedures and the optimization processes, are carried out, in terms of: unit structural weight, diagonal cross section distribution along elevation, deformed configuration, lateral displacements, interstory drift ratio, diagonal strength demand to capacity ratio.